Key melt properties for controlled synthesis of glass beads by aerodynamic levitation coupled to laser heating - Baborak, Jan; Yembele, Maureen; Varak, Petr; Ory, Sandra; Veron, Emmanuel; Pitcher, Michael J. J.; Allix, Mathieu; Nekvindova, Pavla; Zandona, Alessio (International Journal of Applied Glass Science, 2023)
Binary alkali silicate glasses were synthesized as beads by aerodynamic levitation coupled to laser heating to test the applicability of the method to this compositional range. While bubble-free lithium disilicate beads could be easily obtained, sodium and potassium silicates proved more challenging to melt without significant alkali evaporation: the final samples contained bubbles and exhibited compositional drifts compared to the starting stoichiometry, especially at high SiO2 content. The risk of volatilization from the melts was evaluated empirically: the volatility of each oxide component scaled to the ratio between its melting temperature Tm and the Tm of the target composition (revap), while the difference between such ratios (Δevap) provided a qualitative estimation of the risk of differential evaporation. The formulated approach enables to evaluate the suitability of aerodynamic levitation synthesis for a given target glass composition: while low melting temperature and low liquidus viscosity (η < 100 Pa s) represent the primary optimal conditions, more viscous materials can still be prepared without major compositional drifts using a more careful melting procedure, especially if revap and Δevap are minimized.
CRIS-Team Scopus Importer:2023-03-31
Keywords: aerodynamic levitation coupled to laser heating (ADL); alkali silicate glass; glass beads; high-temperature evaporation; viscosity